Possible Role of Akt in Mossy Fiber Sprouting: Akt Activity and CA3 Mossy Fiber Sprouting in a Kainate Model of Epilepsy: Akt Activity and CA3 Mossy Fiber Sprouting in Epilepsy - husna, Machlusil; Handono, Kusworini; Sujuti, Hidayat; Aulanni'am, Aulanni'am (Journal of Tropical Life Science, 2024)
The most prevalent pathological phenomenon observed in patients with epilepsy is hippocampal mossy fiber sprouting (MFS), which is thought to be associated with epileptic progression, such as worsening seizure control, cognitive function, and behavior. MFS is discovered in the dentate gyrus and the hippocampal Cornu Ammon 3 (CA3) area. The CA3 area is involved in memory, so disturbances in that area can affect memory impairment in patients with epilepsy. The mammalian target of rapamycin complex-1 (mTORC1) is also associated with MFS. Akt is an upstream activator of mTORC1 and a downstream target of mammalian target of rapamycin complex-2 (mTORC2) and plays a role in cytoskeleton organization. We analyzed Akt activity and MFS in the CA3 zone in an in vitro model of kainate-induced epilepsy. We divided organotypic hippocampal slice cultures (OHSCs) into a kainate (epilepsy) group and a control (untreated) group. On the 10th day in vitro (DIV), the kainate group was exposed to 8 µM kainic acid for 48 h, diluted in the medium. At 32 DIV, we measured Akt activity through western blotting and CA3 MFS through synaptoporin fluorescence intensity observed using confocal laser scanning microscopy. We found that Akt activity increased significantly (p = 0.000) in the kainate group, and the synaptoporin fluorescence intensity also increased in the stratum oriens of the CA3 area (p = 0.049) in the kainate group. Our findings implied that Akt may play a role in MFS development. Because Akt is a main downstream target of mTORC2, mTORC2 may also be involved in MFS development. Further research is required to clarify these findings.